Estimating historic seabed carbon disturbance by port dredging and aggregate extraction in NW Europe - Ellie Maynard; Zoë A. Roseby; James D. Scourse; Sophie L. Ward; Callum Roberts; Ruth H. Thurstan; Ciarán McLaverty (PLoS ONE, 2026)
The extent to which different human activities disturb seabed carbon, the largest long-term organic carbon reservoir on the planet, is poorly understood. Research to date has focused primarily on bottom trawl fisheries, but industries that target and extract marine sediments are likely to disturb significant masses of sedimentary organic carbon. This can lead to its remineralisation and reduce the capacity of the ocean to absorb atmospheric CO 2 . In this study, we combine archival documents, industry records, and published seabed substrate data, to estimate historical disturbance of sedimentary organic carbon on the Northwest European Shelf (NWES) from port dredging activities and marine aggregate extraction. Monte Carlo simulations were used to provide probabilistic estimates of annual carbon disturbance and associated upper and lower bounds (5th and 95th percentiles, respectively). Based on annual Monte Carlo simulations run between 1995−2021, our results suggest that port dredging over the shelf area disturbed 2.2 ± 0.9 Mt organic carbon year -1 . In the case of marine aggregate extraction, simulations run between 1955−2022, suggest that marine aggregate extraction disturbed 0.4 ± 0.3 Mt organic carbon year -1 . At a country scale, analysis of activities in UK waters suggest that organic carbon disturbance from port dredging and aggregate extraction activities are approximately three orders of magnitude lower than published estimates of disturbance by bottom trawling. Nevertheless, historical and contemporary port dredging and aggregate extraction present substantial and spatially concentrated sources of anthropogenic carbon disturbance that have not been systematically quantified across the Northwest European Shelf until now. These findings therefore address an important knowledge gap and have the potential to inform marine management and conservation strategies aimed at minimising organic carbon loss from the seabed.